Student study group break-even value and adjustment of the educational program portfolio - G. L. Azoev (Вестник университета)
The need to raising the extra-budgetary funding of the university brings to the fore the goal of increasing the admission of applicants under tuition agreements. This is not news for university employees, but, unfortunately, achieving the goal faces a number of unsolved private tasks. First of all, it is unclear what the cost of one study group should be in order to provide all the necessary conditions for the university development, including the salaries of professors and teachers at least twice the average salary of the home region. How, using the answer to this question, to manage the portfolio of educational programs and the admission campaign. The proposed answers to the questions are based on a marketing approach, which presents formulas for calculating the break-even value of a bachelor’s group, an algorithm for determining the structure of the group, recommendations for adjusting the portfolio of programs and calculating the total amount of university income from extra-budgetary admission, ensuring the planned university development.